Problematic Online Gaming and Cyberbullying Perpetration Among Young Adults: A Quantitative Study (Journal of Asian Development Studies, 2025)
There is substantial literature regarding problematic online gaming and cyberbullying perpetration among young adults. However, such studies are rare in Pakistan. Therefore, the objective of this study is to examine the effects of problematic online gaming on cyberbullying perpetration among young adults in Pakistan. The study adopted a cross-sectional correlational design and employed a purposive sampling technique to collect data from 250 individuals aged 18 to 30, all of whom had been using online gaming for at least the past year. Two scales were utilized, including the Gaming Addiction Scale for Adolescents (shorter version) and the perpetration subscale of the Cyberbullying Perpetration and Victimization Questionnaire (used to measure cyberbullying perpetration only). The correlational results indicate that problematic online gaming has a positive and significant association with cyberbullying perpetration. Moreover, problematic online gaming significantly and positively predicts cyberbullying perpetration among young adults in Pakistan. The study provides comprehensive implications for the well-being of young adults.